Baricitinib treatment for hospitalized patients with severe COVID-19 on invasive mechanical ventilation: a propensity score-matched and retrospective analysis - Mao, Yanxiong; Guo, Anyi; Zhang, Ying; Lai, Jianxing; Yuan, Dian; Zhang, Hao; Diao, Wenqi; Chen, Weisong; Yan, Fugui (Frontiers in Medicine, 2025)
IntroductionBaricitinib is a selective inhibitor of Janus kinase (JAK)1 and JAK2, which is associated with clinical improvement in non-severe COVID-19 patients. But in severe COVID-19 patients, the effectiveness of baricitinib is still controversial.MethodsA propensity score-matched and retrospective study was conducted to evaluate the effectiveness of baricitinib in severe COVID-19 patients requiring invasive mechanical ventilation (IMV).ResultsA total number of 48 patients treated with baricitinib were included, and 48 patients were assigned to control group by propensity score matching. The mean ages were high in both group (baricitinib group vs. control group: 78.80 ± 9.04 vs. 82.57 ± 9.27), and most were unvaccinated (62.5% vs. 66.7%. Baricitinib group had a higher proportion of patients with hypertension (73.9% vs. 45.5%, p = 0.006). Control group had higher level of creatine kinase-myocardial band (247.50 vs. 104.50, p = 0.021). Patients in the baricitinib group were more likely to receive nirmatrelvir/ritonavir (39.6% vs. 16.7%, p = 0.017) and intravenous immunoglobin (14.6% vs. 0, p = 0.007). Baricitinib group had significantly lower all-cause 28-days mortality than control group (72.9% vs. 89.6%, p = 0.004).ConclusionThe present study revealed baricitinib reduced 28-days mortality in severe COVID-19 patients on IMV. The effectiveness of baricitinib in treating patients with severe COVID-19 on IMV needs to be further investigated through future studies.